Cochrane Database of Systematic Reviews 2004
DOI: 10.1002/14651858.cd004688
|View full text |Cite
|
Sign up to set email alerts
|

Paraprofessionals for anxiety and depressive disorders

Abstract: Background The established mental health care system does not have the resources to meet the extensive need for care of those with anxiety and depressive disorders. Paraprofessionals partially replacing professionals may be cost-effective. Objectives To investigate the effectiveness of any kind of psychological treatment for anxiety and depressive disorders performed by paraprofessionals. To examine whether the results apply to clinically significant disorders. Search methods CCDANCTR-Studies, EMBASE (ExerptaM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…These services are different from PAIs in that paraprofessional therapists typically need not have personal experience with the problems they are treating; their effectiveness, however, is relevant to the study of PAIs because it speaks to whether people with little or no prior training as mental health providers may be able to effectively deliver psychosocial treatments. Den Boer et al (2005) meta-analyzed controlled studies of paraprofessional treatments for anxiety and depression. They found that the outcomes achieved by paraprofessionals delivering a variety of cognitive-behavioral and supportive interventions were not statistically different from those achieved by mental health professionals and were significantly better than waitlist and placebo control conditions.…”
Section: Effectiveness Of Nonprofessional Mental Health Servicesmentioning
confidence: 99%
“…These services are different from PAIs in that paraprofessional therapists typically need not have personal experience with the problems they are treating; their effectiveness, however, is relevant to the study of PAIs because it speaks to whether people with little or no prior training as mental health providers may be able to effectively deliver psychosocial treatments. Den Boer et al (2005) meta-analyzed controlled studies of paraprofessional treatments for anxiety and depression. They found that the outcomes achieved by paraprofessionals delivering a variety of cognitive-behavioral and supportive interventions were not statistically different from those achieved by mental health professionals and were significantly better than waitlist and placebo control conditions.…”
Section: Effectiveness Of Nonprofessional Mental Health Servicesmentioning
confidence: 99%
“…There is indeed much evidence to support this notion. For example, in a recent meta-analysis, den Boer, Wiersma, Russo and van den Bosch (2005) found that paraprofessionals such as volunteers, graduate students, ex-clients, and members of self-help organizations, were as effective in treating anxiety and depression as professionals; the results could not be attributed to poor study methodology, and differences between professionals and paraprofessionals failed to appear even at long term follow up. The evidence strongly indicates that untrained 'paraprofessionals' are as effective as, if not more effective than, professionals who have had extensive training and experience and who hold high levels of formal qualifi cations.…”
Section: The Therapist-client Relationship Re-visitedmentioning
confidence: 99%
“…Furthermore, most mental health interventions are delivered by professional facilitators (e.g., nurses and social workers), and few are implemented by trained paraprofessional behavioral interventionist or lay health workers . Paraprofessionals are often socioculturally competent as they are ethnically, culturally, linguistically, and experientially similar to the target patient or study population .…”
Section: Introductionmentioning
confidence: 99%